The Forex trading course : a self-study guide to becoming a successful currency trader - Cofnas, Abe, 1950- (John Wiley & Sons, Inc., 2015)
EXPERT, DEPENDABLE FOREX COACHING--UPDATED TO KEEP YOU AHEAD IN AN EVOLVING MARKET The Forex Trading Course is the systematic guide aspiring traders need to enter the market with the confidence and skills necessary to generate wealth. Masterfully written so both basic and complex concepts are readily accessible, this all-inclusive training tool outlines a practical course of action to develop strategies integrating fundamental and technical analysis. It also demonstrates how to identify high-probability patterns and trades, adjust your trading plan for different account sizes, use emotional intelligence to improve trading performance, and much more. This second edition is fully revised to address: Changes brought about by quantitative easing and central bank intervention--including greater spikes and disruptions in the forex and the influence of global growth and inflation on the market Using binary options with forex trades to make accurate predictions on direction, targets, and stops Social media trading and how to navigate herding behavior and swarming patterns The latest insights and trends in cryptocurrencies such as Bitcoin Complete with practice assignments to reinforce the material and a supplemental website to enhance your knowledge, The Forex Trading Course, Second Edition unlocks your optimal potential for profitable currency trading.